Decoding short-term fertility intentions: exploring the nexus of gender equality and societal factors in a comparative EU gender regimes analysis - Aragón-Morales, Alba-María; Ruiz-Jiménez, Antonia-María (Frontiers in Sociology, 2025)
BackgroundPersistently low fertility in the European Union has drawn attention to the gap between desired and intended fertility, often linked to enduring gender inequalities. Clarifying how individual, partner, and contextual factors jointly shape short-term fertility intentions can inform policy across diverse gender regimes. Objective: To examine short-term fertility intentions among partnered individuals in Finland, Germany, and Spain, representing Scandinavian, Continental, and Mediterranean gender regimes, respectively.MethodsWe use harmonized data from the Generations and Gender Survey (GGS) and Spain’s National Institute of Statistics (INE). We apply Classification and Regression Trees (CART) to capture non-linear interactions among individual, partner, and contextual factors (including employment status, caregiving responsibilities, and gender values), and to identify profiles associated with higher vs. lower short-term intentions to have a child.ResultsFamily size, caregiving burdens, and economic stability emerge as central determinants of fertility intentions, with marked gendered and contextual differences across countries. Patterns are particularly pronounced among individuals with no children or one child, where combinations of stable employment and lower caregiving loads align with higher intentions, while economic insecurity and heavier (gendered) care burdens depress intentions. CART uncovers country-specific thresholds and configurations consistent with each gender regime.ConclusionShort-term fertility intentions reflect unmet gender-mediated needs and serve as an early indicator of latent potential for social and political mobilization. Our findings highlight the influence of gender regimes on reproductive decision-making and support policies that address structural inequalities, especially in employment and care, to enable the realization of reproductive desires across heterogeneous socioeconomic contexts.